Integrasi Konsep Pengalaman Belajar John Dewey Dalam Pembelajaran Al-Qur'an Anak - Fathoni, Tamrin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this study is to analyze the integration of John Dewey's experiential learning concept in children's Qur'an learning in order to increase their active involvement and understanding of Qur'anic values. This study uses a library research method to collect and analyze data from various literature sources, such as books, journal articles, and documents related to John Dewey's experiential learning concept and its application in Qur'anic education. The data obtained are analyzed through identification of key concepts, comparison with the principles of Qur'anic education, and categorization to build a systematic theoretical framework. This approach provides a strong theoretical basis for evaluating the relevance and potential of integrating Dewey's theory in children's Qur'anic learning. The results of the study indicate that the application of John Dewey's experiential learning concept in Qur'anic learning can create a more active and contextual learning experience for children. With the